The Historical Development of the Law Concerning Demonstrations in Russia - Evgenyi Anatolevich Mosolov (Сибирское юридическое обозрение, 2011)
The article is devoted to the of a constitutional right to carry out public events by citizens of Russian Federation. Historical aspect allows us to observe the way constitutional right to carry out public events is regulated and at the same time the scale of democratization of a society. Today we have federal law, which was legislated to define concretely the regulations of the constitution of Russian Federation. And it is a great step for regulating the constitutional right to carry out public events in Russia.